A practical perspective of fluid (gas or liquid) - Solid adsorption equilibrium - Sircar, Shivaji (Separation and purification technology, 2020)
•The pure and multicomponent fluid (gas and liquid) – solid adsorption equilibria is a core variable for establishing the performance of an adsorptive separation process as well as for selection of an optimum adsorbent for a separation duty. Factors like the nature of the adsorbate-adsorbent system, the system temperature, the adsorbent porosity and the energetic homogeneity or heterogeneity of the adsorbent govern the shape of an adsorption isotherm.•The equilibrium adsorption isotherms are used to determine (a) the selectivity of adsorption between the components of a mixture, (b) the heat effects associated with the ad(de)sorption process, and (c) the driving force for adsorbate transport from the bulk fluid phase int the adsorbent particle. Analytical adsorption isotherm models are required for calculation of these properties and to facilitate numerical solution of a process performance model.•The isotherm models must satisfy several physical and thermodynamic constraints to be practically useful.•A list of analytical isotherm models covering porous and non-porous and homogeneous and heterogeneous adsorbents is presented.•Estimation of multicomponent adsorption equilibria from the corresponding pure component isotherms employing various engineering models and use of characteristic curves for coalescing isotherms of different gases at different temperatures on the same adsorbent for predictive purposes should be handled with care. These procedures must be validated using experimental data for the system of interest before their use. The fluid (gas or liquid) – solid adsorption equilibrium is a core thermodynamic property of an adsorbate-adsorbent system for establishing the efficiency of separation of a fluid mixture by an adsorptive process and for selection of an optimum adsorbent for a specified separation duty. The shape of an equilibrium adsorption isotherm of a pure gas or those for the components of a gas mixture are determined by the nature of the adsorbate-adsorbent pair, the system temperature, the porosity of the adsorbent, and the energetic heterogeneity of the adsorbent. The same factors also determine the shape of an equilibrium isotherm of a binary liquid mixture. The published literature on this subject is vast. The purpose of this article is not to review the literature but to provide a systematic practical perspective of the subject. Analytical models for fluid-solid adsorption isotherms facilitate numerical simulation of separation process performance using mathematical process models. However, the practically viable isotherm models must obey several physical and thermodynamic constraints. A selection of such isotherm models for pure and multi-component gas and binary liquid mixtures is presented. It may not, however, be possible to a priori chose a reliable isotherm model for a system of interest without extensively testing the model using experimental isotherm data for that system. The same conclusion applies to theoretical concepts for (a) predicting multi-component gas-solid adsorption equilibria from the corresponding pure gas adsorption equilibria, (b) coalescing adsorption isotherms of different pure gases at different temperatures and (c) coalescing isotherms for adsorption of trace components from a mixture (gas or a liquid) into a single characteristic curve on a given adsorbent for predictive purposes.